1994
DOI: 10.1159/000246865
|View full text |Cite
|
Sign up to set email alerts
|

Angiodysplastic Syndrome with Capillary and Venous Malformation Associated with Soft Tissue Hypotrophy

Abstract: Angiodysplastic syndromes include a vascular malformation which may often be associated with secondary changes such as further vascular abnormalities, soft tissue and bone hypertrophy. One of the best known is the syndrome triad originally described by Klippel and Trenaunay, which includes a unilateral capillary malformation, ectatic veins and osseous and soft tissue hypertrophy. A female patient is reported who had an extensive capillary malformation, discrete ectatic veins overlying an extensive venous malfo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
1

Year Published

1996
1996
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 11 publications
0
7
1
Order By: Relevance
“…An atypical hypotrophic variant of KTS has also been described. 2,12 Two of the patients with KTS included in the current series had hypotrophy of the upper limb with bone involvement; one of these had hemicorporal distribution of port-wine stains and hand involvement with macrodactyly, ectrodactyly, and syndactyly, whereas the other patient showed port-wine stains that mainly affected the lower limbs and had upper limb and hand hypotrophy, with clinodactyly and camptodactyly.…”
Section: Discussionmentioning
confidence: 91%
“…An atypical hypotrophic variant of KTS has also been described. 2,12 Two of the patients with KTS included in the current series had hypotrophy of the upper limb with bone involvement; one of these had hemicorporal distribution of port-wine stains and hand involvement with macrodactyly, ectrodactyly, and syndactyly, whereas the other patient showed port-wine stains that mainly affected the lower limbs and had upper limb and hand hypotrophy, with clinodactyly and camptodactyly.…”
Section: Discussionmentioning
confidence: 91%
“…These results could be of significance to explain illnesses that appear in the vascular system in only one body half, like Sturge-Weber syndrome or Klippel-Tr6nannay syndrome. The syndrome triad of the latter includes unilateral capillary malformations, ectatic veins and osseous and soft tissue hypertrophy (Bircher et al 1994;Huang and Creath 1994). The next question to be answered is the nature of the barrier -which chemical substances are involved and how they are genetically determined.…”
Section: Discussionmentioning
confidence: 99%
“…We believe our cases expand the spectrum of associations with this type of CM. This clinical entity seems to be infrequent, as we could only find a few previous cases described in the literature 8‐10 . Bircher et al reported a 30‐year‐old woman with an extensive CM associated with non‐progressive ipsilateral undergrowth 8 .…”
Section: Discussionmentioning
confidence: 78%